RECONCEPTUALIZING TAX ADMINISTRATION IN NIGERIA: THE IMPERATIVE OF A SPECIALIZED TAX ENFORCEMENT COMMISSION - Oyeniran, Oyeleke S.; Adegbite, Aderonke; Olumayowa, Osilojo (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2025)
In Nigeria, combination of tax legislations provides punitive measures for tax defaulters. However, enforcing these sanctions necessitates pro cedures like arrests, investigations, detentions, and prosecutions. A major hurdle lies in the fact that, while the responsibility for these processes falls on the shoulders of tax authorities, they aren't equipped with inherent police powers. As a result, their effectiveness often relies on collaborations with the Police and other law enforcement bodies. Unfortunately, these entities, already grappling with internal complexities, find themselves stretched thin amidst Nigeria's escalating insecurity challenges. This paper adopts the doctrinal research method and relies on the primary and secondary sources of Nigerian Laws. The aim of this paper is to delve deep into the intricacies of tax crime enforcement in Nigeria, analyzing the current collaboration dynamics. In light of the evident challenges and inefficiencies, it underscores the pivotal recommendation of establishing a new, sui generis police force, akin to the Economic and Financial Crimes Commission (EFCC), dedicated solely to tax enforcement. This dedicated entity would streamline tax law enforcement, ensuring rigorous oversight and more efficient prosecution of tax-related crimes.